Sustainable disclosure versus ESG intensity: Is there a cross effect between holding and SRI funds?. (21st July 2021) - D'Apice, Vincenzo; Ferri, Giovanni; Intonti, Mariantonietta
Abstract: Sustainable and Responsible Investment (SRI) funds – the largest component of the fast‐expanding sustainable financial investment industry – apply environmental, social and governance (ESG) analyses to manage their investment portfolios and are particularly demanding in terms of issuers' disclosure. In this paper we take a step forward and ask whether adopting high‐quality sustainability disclosure is important also for SRI funds' holding companies. Specifically, we introduce a novel metrics on the extent of holding companies' sustainability disclosure based on the quality of their Global Reporting Initiative (GRI) reporting. In parallel, we use a standard approach to measure a fund's ESG intensity, that is, the weighted ESG average of a fund's investments. Indeed, we find that an SRI fund's ESG intensity systematically improves when the associated holding company improves its GRI sustainability disclosure. Moreover, we show that this positive effect of holdings' disclosure on a fund's ESG intensity is larger in jurisdictions with less stringent regulation on disclosure, where the signaling value of GRI disclosure is supposedly heightened. Our results do not seem to be driven by endogeneity between a fund's ESG intensity and its holding company's GRI reporting. First, a fund's ESG investment policy and its holding company's sustainability disclosure policy lie on separate decision ladders. Second, we show that the two variables are empirically uncorrelated. Third, our results prove resilient to a battery of robustness checks. The implication of our finding is that holding companies' sustainability disclosure engagement can reap a benefit for their managed SRI funds – provided ESG ratings are reliable –, whose enhanced credibility might prove a key competitive factor.